A new leptochelioid family, Heterotanoididae (Crustacea: Peracarida: Tanaidacea), and a new species of Heterotanoides from New Zealand - Bird, Graham J. (Zootaxa, 2012)
A new species of Heterotanoides is described from Waiheke Island, in the warm Aupourian zoogeographic province of New Zealand, and its relationships to other members of the genus are discussed. New characters for Heterotanoides, such as plumose epimeral setae, cap-like antennule segment, and four-spined maxilliped endites are presented, and their phylogenetic relevance examined. Based on phylogenetic analyses of Heterotanoides, leptocheliids, pseudozeuxids, teleotanaids, and some nototanaids, a new family is established for the genus: Heterotanoididae.